2017
DOI: 10.1002/ange.201708927
|View full text |Cite
|
Sign up to set email alerts
|

Conotoxin Φ‐MiXXVIIA from the Superfamily G2 Employs a Novel Cysteine Framework that Mimics Granulin and Displays Anti‐Apoptotic Activity

Abstract: Conotoxins are al arge family of disulfide-rich peptides that contain unique cysteine frameworks that target ab road range of ion channels and receptors.W er ecently discovered the 33-residue conotoxin F-MiXXVIIA from Conus miles with an ovel cysteine framework comprising three consecutive cysteine residues and four disulfide bonds. Regioselective chemical synthesis helped decipher the disulfide bond connectivity and the structure of F-MiXXVIIA was determined by NMR spectroscopy. The 3D structure displays auni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…As a consequence, the third disulfide bond (Cys III -Cys VI ) of VxXXB-C(21-50), which typically threads the loop formed by the first two disulfide bonds to make a knot in the ICK fold (Figure 2B), instead links the β3 loop with the unstructured C-terminal region (Figure 2A). This tertiary structure resembles the N-terminal of the cell proliferation regulator human granulin A (Tolkatchev et al, 2008) and has been previously reported in conotoxins N ext H-Vc7.2 and ϕ-MiXXVIIA (Jin et al, 2017;Nielsen et al, 2019). Indeed, with a large second β-hairpin, VxXXB-C(21-50) superimposes the N-terminal of human granulin A (RMSD 2.23 Å), N ext H-Vc7.2 (RMSD 3.82 Å) and ϕ-MiXXVIIA (RMSD 2.79 Å).…”
Section: The Vxxxb-c(21-50)/ls-achbp Complexsupporting
confidence: 77%
See 1 more Smart Citation
“…As a consequence, the third disulfide bond (Cys III -Cys VI ) of VxXXB-C(21-50), which typically threads the loop formed by the first two disulfide bonds to make a knot in the ICK fold (Figure 2B), instead links the β3 loop with the unstructured C-terminal region (Figure 2A). This tertiary structure resembles the N-terminal of the cell proliferation regulator human granulin A (Tolkatchev et al, 2008) and has been previously reported in conotoxins N ext H-Vc7.2 and ϕ-MiXXVIIA (Jin et al, 2017;Nielsen et al, 2019). Indeed, with a large second β-hairpin, VxXXB-C(21-50) superimposes the N-terminal of human granulin A (RMSD 2.23 Å), N ext H-Vc7.2 (RMSD 3.82 Å) and ϕ-MiXXVIIA (RMSD 2.79 Å).…”
Section: The Vxxxb-c(21-50)/ls-achbp Complexsupporting
confidence: 77%
“…Granulins are ancestral ~55-residue growth factors responsible for development and wound healing. The N-terminal ~30 residues of granulins includes the characteristic core granulin fold identified previously in conotoxins Φ-MiXXVIIA and N ext H-Vc7.2 as a mini-granulin fold distinct from the ICK toxin fold (Tolkatchev et al, 2008;Palfree et al, 2015;Jin et al, 2017;Nielsen et al, 2019). Indeed, mini-granulin-fold proteins (Sheng et al, 2008) were used by AlphaFold to model VxXXB from human and Drosophila E3 ubiquitin-protein ligase protein (Ho et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The crude linear peptide was purified by preparative RP-HPLC (Vydac C18). For the one-pot regioselective formation of the 1–3 and 2–4 (or 1–4, 2–3) disulfide bonds, the method has been described before [ 45 ]. Briefly, the crude dithiol product was first subjected to a 5 min I 2 treatment in 90% AcOH/MeOH to form the Cys 2–4 or Cys 2–3 disulfide bond.…”
Section: Methodsmentioning
confidence: 99%
“… a The linear peptide comprised four different sets of S -protected Cys residues. (a) I 2 /AcOH, MeOH (9:1), 5 min, (b) I 2 /45% AcOH, 5% MeOH and 0.5% TFA, 90 min, (c) HF/ p -cresol, 0 °C, 1h followed by I 2 /0.1% TFA/50% MeCN/H 2 O, 5 min, (d) NH 4 I/DMS/TFA, 0 °C, 30 min (* = the arrangement of the disulfide bonds doesn’t pertain to a specific conformation) (ref ). …”
Section: Safety Catch Protecting Groupsmentioning
confidence: 99%